Low Dose Infliximab for Prevention of Postoperative Recurrence of Crohn’s Disease: Long Term Follow-Up and Impact of Infliximab Trough Levels and Antibodies to Infliximab - Sorrentino, Dario; Marino, Marco; Dassopoulos, Themistocles; Zarifi, Dimitra; Del Bianco, Tiziana (PloS one, 2015)
In patients with postoperative recurrence of Crohn's disease endoscopic and clinical remission can be maintained for up to 1 year with low infliximab doses (3 mg/Kg). However, in theory low-dose infliximab treated patients could develop subtherapeutic trough levels, infiximab antibodies, and might loose response to therapy. To verify this hypothesis infliximab pharmacokinetics and clinical/endoscopic response were checked in a group of patients treated in the long term with low infliximab doses. Infliximab antibodies, infliximab levels, highly-sensitive CRP and fecal calprotectin were measured during the 8-week interval in 5 consecutive patients in clinical (Crohn's Disease Activity Index < 150) and endoscopic (Rutgeerts scores 0-1) remission after one year of therapy with infliximab 3 mg/Kg. For comparison with reported standards, infliximab pharmacokinetics and inflammatory parameters were also tested in 6 Crohn's disease patients who did not undergo surgery and who were in clinical remission while on infliximab 5 mg/Kg. Patients on low infliximab dose also underwent colonoscopy after 18 additional months of therapy. Highly sensitive CRP and fecal calprotectin increased in all patients during the 8-week interval. Infliximab trough levels were lower in patients treated with the low dose compared to controls (mean±SE: 2.0±0.3 vs 4.75±0.83 μg/mL respectively p<0.05). Infliximab antibodies were present in two of the subjects treated with low infliximab dose and in none of the controls. However, in low dose-treated patients after 18 additional months of therapy endoscopy continued to show mucosal remission and none of them developed clinical recurrence or side effects. Patients treated with low infliximab doses had lower trough levels compared to patients treated with 5 mg/Kg and some developed antibodies to infliximab. However, low infliximab doses sustained clinical and endoscopic remission for a total of 30 months of treatment.